2017
DOI: 10.18632/oncotarget.21155
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 and PD-1 mediated inhibition of antitumor CTL responses in the human tumor microenvironment

Abstract: Accumulating evidence indicates that inflammation plays a critical role in cancer development; however, mechanisms of immunosuppression hinder productive anti-tumor immunity to limit immunopathology. Tumor-specific cytotoxic T lymphocyte (CTL) dysfunction or exhaustion by upregulating inhibitory receptors such as programmed cell death 1 (PD-1) in tumor-bearing hosts is one such mechanism. Identification and blockade of the pathways that induce CTL dysfunction has been shown to partially restore CTL function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Recently, several studies have demonstrated an association between PGE 2 elevation and upregulated expression of other immunoinhibitory molecules, such as PD-1, in human cancer (53,54). In addition, dual blockade of PGE 2 and PD-1 improved tumor eradication in a mouse model (55).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have demonstrated an association between PGE 2 elevation and upregulated expression of other immunoinhibitory molecules, such as PD-1, in human cancer (53,54). In addition, dual blockade of PGE 2 and PD-1 improved tumor eradication in a mouse model (55).…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of COX2–PGE 2 signaling by COX‐2 inhibitors or antagonists of PGE 2 receptors enhance the effect of PD‐1 blockade, suggesting that the COX‐2–PGE 2 axis has antagonizing effects on PD‐1 inhibitors . Interestingly, the TLR9 agonist upregulates COX‐2 expression through nuclear factor‐κB activation .…”
Section: Discussionmentioning
confidence: 99%
“…5 The disruption of COX2-PGE 2 signaling by COX-2 inhibitors or antagonists of PGE 2 receptors enhance the effect of PD-1 blockade, suggesting that the COX-2-PGE 2 axis has antagonizing effects on PD-1 inhibitors. 6 Interestingly, the TLR9 agonist upregulates COX-2 expression through nuclear factor-jB activation. 7 Therefore, when the TLR9 subfamily agonist is delivered concomitantly with PD-1 inhibitors, the agonist may counteract the anticancer property of PD-1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Combined blockade of COX-PGE 2 signalling and PD-1/PD-L1 augments T cell responses and improves control of viral infection and tumour growth (J. H. Chen et al, 2015;Miao et al, 2017;Sajiki et al, 2019).…”
Section: Pge 2 On T Cell Functionsmentioning
confidence: 99%